Predictors of Smoking Cessation Medication Use among Nonobese and Obese Smokers. (12th May 2014) - Yang, Mo; Mehta, Hemalkumar B.; Bhowmik, Debajyoti; Essien, Ekere James; Abughosh, Susan M.
<x xml:space="preserve">Abstract</x> The objective of this study was to identify and compare the predictors of smoking cessation medication use among obese and nonobese adult smokers. A retrospective cross-sectional study was conducted using the Medical Expenditure Panel Survey (MEPS) data (2008–2009). The study participants included smokers aged 18 years and older who self-reported their smoking status as smoker. The outcome variable was utilization of any Food and Drug Administration approved smoking cessation medication (varenicline, bupropion, and nicotine replacement therapy). Multivariable logistic regression analyses were conducted. A total of 82.20 million (weighted sample size for two years) adult smokers were included; of which nearly 30% were obese-smokers. The use of smoking cessation medication was 2.66% and 5.17% among nonobese and obese smokers, respectively. Multivariable logistic regression results showed that race/ethnicity, health insurance coverage, prescription insurance coverage, usual source of health care, urban residence, region, Charlson comorbidity index, and instrumental activities of daily living (IADL), were significant predictors of using smoking cessation medications. The overall smoking cessation medication use rate was low implying limited compliance to guideline. Predictors identified in this study should be taken into consideration in health promotion programs that are designed to optimize the utilization of these smoking cessation medications.